2009
DOI: 10.1007/s00425-009-0963-x
|View full text |Cite
|
Sign up to set email alerts
|

Label-free in situ imaging of lignification in the cell wall of low lignin transgenic Populus trichocarpa

Abstract: Chemical imaging by confocal Raman microscopy has been used for the visualization of the cellulose and lignin distribution in wood cell walls. Lignin reduction in wood can be achieved by, for example, transgenic suppression of a monolignol biosynthesis gene encoding 4-coumarate-CoA ligase (4CL). Here, we use confocal Raman microscopy to compare ligniWcation in wild type and lignin-reduced 4CL transgenic Populus trichocarpa stem wood with spatial resolution that is sub-m. Analyzing the lignin Raman bands in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 37 publications
(71 reference statements)
1
53
0
Order By: Relevance
“…The kinetic properties (Table III) and genetic functions of Ptr4CL3 (Schmidt et al, 2009) demonstrate that Ptr4CL3 is an ortholog of Pt4CL1 characterized previously (Hu et al, 1998(Hu et al, , 1999Harding et al, 2002). Orthologs of Ptr4CL3 have been identified and characterized for other Populus spp.…”
Section: Discussionmentioning
confidence: 61%
“…The kinetic properties (Table III) and genetic functions of Ptr4CL3 (Schmidt et al, 2009) demonstrate that Ptr4CL3 is an ortholog of Pt4CL1 characterized previously (Hu et al, 1998(Hu et al, , 1999Harding et al, 2002). Orthologs of Ptr4CL3 have been identified and characterized for other Populus spp.…”
Section: Discussionmentioning
confidence: 61%
“…Raman signatures of the phenolic monolignols will be registered at 1,600 cm −1 (aromatic), the carbonyl and unsaturated carbon double bonds at 1,735 cm −1 and 1,650 cm −1 , respectively. Thus, chemical imaging by confocal Raman microscopy was used for the spatial distribution of cellulose and lignin in wood walls in situ [160]. A review by Agarwal [159] summarizes the use of Raman spectroscopy for plant cell imaging.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…), beech (Fagus sylvatica) and oak (Quercus robur) (Lehringer et al 2008). Schmidt et al (2009) studied the lignification in wild-type and lignin-reduced 4CL transgenic Populus trichocarpa stem wood and showed that transgenic reduction of lignin is particularly pronounced in the S2 wall layer of fibres .…”
Section: Uv-vis Spectra Of Lignin and Other Ring Structuresmentioning
confidence: 99%